Proposal for the calculation of the Ordinal Alpha and Armor Theta - Domínguez Lara, Sergio (2012)
The present article presents a program in MS Excel format for the calculation of the coefficient Ordinal Alpha and Armor Theta, used to quantify the reliability in ordinal response items. The construction of the commandos was made based on the polychoric correlation matrix of the program FACTOR (Lorenzo & Ferrando, 2007). The suitable use of these methods and their lack of implementation in traditional statistical packages justifies its construction like a tool for the investigator in psychology, discipline in which is common the use of Pearson correlation matrix with the limitations that this carries (it assumes that the studied variable is continuous). It is discussed the use and the limitations of the tool.